Non-Performing Assets of North Malabar Gramin Bank - P. P. Lakshmanan (Commerce Spectrum, 2014)
North MalabarGramin Bank (NMGB) has been playing a dominant role in the economic development of Kerala. It is functioning in the area covering seven districts viz; Kasargod, Kannur,Wayanad,Ernakulam, Kottayam, Alappuzha and Kollam. Its functions spread over both urban and rural areas. NMGB ensures accelerated growth in the rural development. However, the bank faces the problems of overdue. Since 1995, banks in India have made provisions for NPA in order to avoid heavy burden in future. The private banks and new generation banks provide diversified banking facilities and other value added services to its customers. It poses a threat to regional rural banks. This study makes an attempt to analyse the volume and intensity of Non Performing Assets (NPAs) and the impact it has on the profitability of North Malabar Gramin Bank.